Energieffektiviteten hos konverterade kylanläggningar ombord på fartyg - En studie om konverteringsalternativ för maritima kylanläggningar - Frejd, Tommy; Himmelmann, Olof (My University, 2017)
Onboard all Ro-Pax vessels there is a refrigerant plant containing some type of refrigerant. Most refrigerants have a negative impact on the environment, some contribute to the greenhouse effect, and some are also harmful to the ozone layer. International regulations for marine refrigeration plants only prohibit the use of refrigerants that affect the ozone layer. Refrigerants that contribute to the greenhouse effect are not regulated by international regulations, but Swedish authorities have chosen to apply EU regulations for land-based refrigeration plants to Swedish-registered vessels. New EU regulations will come into force in 2020 regarding the use of refrigerants with a major impact on the greenhouse effect, which will affect the Swedish-flagged vessels. Therefore, it is important to study different conversion options for existing refrigeration plants. This study intends to theoretically investigate how energy efficiency and overall climate impact are affected when converting a provision refrigeration plant with R404A as a refrigerant, as well as investigating the suitability of various refrigerants as conversion options with regard to cooling properties and environmental impact. The work has been carried out in the form of a case study of a refrigeration plant onboard a Ro-Pax vessel where the purpose is to use the plant as a reference to carry out theoretical calculations with alternative refrigerants. Through the collection of operating data and information about the reference plant, the performance of the plant is calculated. Thereafter, the plant's performance is calculated for alternative refrigerants that have a lower greenhouse effect than the current refrigerant of the plant. The refrigerants investigated in the study resulted in better energy efficiency and less overall climate impact than the R404A. Refrigerants; R407C, R407F, R454A, R449A, R455A, R448A and R442A are potential conversion options for the reference facility, as they have good characteristics and less climate impact. Continuous studies should include more detailed analyses regarding what needs to be addressed in existing refrigeration plants for a suitable conversion.
Keywords: Energi; Transport; Hållbar utveckling; Farkostteknik; Energy; Transport; Sustainable Development; Vehicle Engineering